Characterisation of cholinesterase from kidney tissue of Asian sea bass (Lates calcarifer) and its inhibition in presence of metal ions - Hayat, NM; Ahmad, SA; Shamaan, NA; Sabullah, MK; Shukor, MYA; Syed, MA; Khalid, A; Khalil, KA; Dahalan, FA (Triveni Enterprises, 2024)
Indexed by WOS